Lactobacillus rhamnosus Probiotic Food as a Tool for Empowerment Across the Value Chain in Africa - Westerik, Nieke; Kort, Remco; Sybesma, Wilbert; Reid, Gregor (Frontiers in Microbiology, 2018)
Perhaps by serendipity, but Lactobacillus rhamnosus has emerged from the 1980s as the most research probiotic species. The many attributes of the two main probiotic strains of the species, L. rhamnosus GG and GR-1, have made them suitable for applications to developing countries in Africa and beyond. Their use with a Streptococcus thermophilus starter strain C106, in the fermentation of milk, millet, and juices has provided a means to reach over 250,000 consumers of the first probiotic food on the continent. The social and economical implications for this translational research are significant, and especially pertinent for people living in poverty, with malnutrition and exposure to environmental toxins and infectious diseases including HIV and malaria. This example of probiotic applications illustrates the power of microbes in positively impacting the lives of women, men and children, right across the food value chain.